Métodos de Identificação de Zonas de Acumulação de Acidentes: Análise e Aplicação do HSM - Sara Ferreira (2013)
This paper presents a description of the various methods proposed by the Highway Safety Manual to identify hotspots. In fact, this manual has become a tool for the professional in road safety all over the world. Therefore, the main goal of this paper is to describe and organize those methods to help safety professionals to select the method(s) to apply to the study case. Thus, the various methods are organized based on 3 application criteria. In addition, an application to the Porto city is presented considering some of the manual methods as well as a recent method namely probabilistic method. A comparison of the various methods is developed using tests to assess the performance of each method. The methods named Excess Predicted Average Crash Frequency proposed by the manual and the Binary Probit Model, recently developed, present the best results based on those tests. The results of the case study application may be the basis for future applications in other regions and/or countries.